Content Analysis of Musical Art Materials In Arts and Culture Textbook - Isabel Coryunitha Panis; Agustinus Beda Ama; Stanis Sanga Tolan (Unika Santu Paulus Ruteng, 2024)
Education is a conscious and planned effort to create complete learning outcomes to develop students' abilities. Effective and efficient learning can be realized if the availability of teaching materials. Teaching materials have a more effective role because they can facilitate the implementation of learning in the classroom. Teaching materials used during the learning process are called textbooks. The components of teaching materials in the curriculum must appear in the elaboration according to Competency Standards (SK), Basic Competence (KD) and Competency Achievement Indicators. The purpose of this study was to determine the feasibility of the content and presentation of a Musical Arts textbook in a Cultural Arts Textbook. The method used in this research is content analysis where the emphasis is on: how the researcher looks at the constancy of the content of communication, which in this case is the contents of a qualitative art and culture textbook, how the researcher interprets the contents of the textbook, reads the symbols, interpret the contents and see the usefulness of the contents of the book. And, the results of this study found that the characteristics of the 2013 curriculum lie in the competence of graduates. The competency is an outcomes-based curriculum. The 2013 curriculum competencies are as follows: Curriculum content or content is expressed in the form of class Core Competencies (KI) and further detailed in Basic Competency (KD) subjects. Core Competency (IC) is a categorical description of competence in the aspects of attitudes, knowledge and skills